OS-Learn: mobile learning application for operating system with augmented reality / Alif Faisal Ibrahim and Muhammad Hazman Yussri - Ibrahim, Alif Faisal; Yussri, Muhammad Hazman (UiTM Cawangan Perlis, 2020)
Theoretical subjects or courses are often disliked among students due to its massive load of information which often lead to misconception or confusion. As a result, most students would resolve to rote learning instead. Therefore, the purpose of this research is to design and develop OS-Learn, a mobile application created to help students in learning theoretical subjects such as operating systems concepts. The core element of OS-Learn would be active engagement, such as the use of visualization and improving memory retention. OS-Learn use AR elements as part of its visualization technique. ADDIE model was selected as the framework to design and develop the application. User acceptance testing was performed after the development phase to obtain feedback from potential users which are university students. Thirty students were selected to evaluate the mobile app based on its design, navigation, and content. Each respondent was given set of tasks and were required to complete a questionnaire based on their experience using the application. The outcome was mostly positive where most respondents were satisfied with the overall design of the mobile application. Feedback and suggestions were also collected then reviewed to make necessary adjustments to the application before being deployed.